Blood, sweat & tears : becoming a better surgeon - Stahel, Philip F. (Online access with DDA: Askews (Medicine), 2016)
All surgeons want to be better surgeons ... They work hard to be respected by their peers, appreciated by their patients, and valued by their communities. Most of the estimated 200 million surgeries performed worldwide every year go as anticipated, with positive patient outcomes. However, the number of surgical complications and preventable medical errors still remains unacceptably high. Why are experienced surgeons still creating so many adverse events? More importantly, what can surgeons do to better address the situation? This book seeks to answer these questions. The book provides pragmatic examples on how good surgeons can grow from being technically brilliant to becoming empathetic and capable of providing safe, compassionate, and more effective patient care. The book follows trauma surgeon Philip Stahel's 20-year journey from his 'rookie years' in internship and residency, to his development as a global patient safety advocate, renowned academician and teacher, and compassionate surgeon. The book touches on why our current patient safety protocols and checklists fail to keep patients safe and how a physician-driven initiative with credible leadership is needed to build a sustainable 'culture of patient safety'. Written for a wide audience and based on the paradigm that "good judgment comes from experience which comes from poor judgment", the book provides in-depth coverage of all the critical and timely components of safe surgical care, relates practical tips for improving the quality of partnerships between surgeons and patients, and offers a practical guide on how to reduce the learning curve to becoming a better surgeon